2018
DOI: 10.1080/01652176.2018.1482028
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia psittaciandC. aviumin feral pigeon (Columba livia domestica) droppings in two cities in the Netherlands

Abstract: C. psittaci and C. avium are present in feral pigeon droppings in Utrecht and Haarlem. Human contact with droppings from infected pigeons or inhalation of dust from dried droppings represent a potential hazard to public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
18
0
7
Order By: Relevance
“…C. ibidis are three newly described avian chlamydial species. Thus far, C. avium has been detected in pigeons and psittacine birds, whereas C. gallinacea is endemic in domestic poultry, and is capable of infecting chickens, ducks, guinea fowls, turkeys, and possibly other birds [12,13,22,23,158,166,167,168,169,170,171]. Thus far, feral sacred ibis is the sole known animal reservoir for Ca.…”
Section: Introductionmentioning
confidence: 99%
“…C. ibidis are three newly described avian chlamydial species. Thus far, C. avium has been detected in pigeons and psittacine birds, whereas C. gallinacea is endemic in domestic poultry, and is capable of infecting chickens, ducks, guinea fowls, turkeys, and possibly other birds [12,13,22,23,158,166,167,168,169,170,171]. Thus far, feral sacred ibis is the sole known animal reservoir for Ca.…”
Section: Introductionmentioning
confidence: 99%
“…C . avium , another chlamydial species infecting birds, was first described in 2014 [16] and has so far been reported in feral pigeons from Italy, France, Germany and the Netherlands, in a parrot from Germany and in a mallard from Poland [1618]. To date, it is still unclear whether it causes disease in birds, if it has zoonotic potential or how it is transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…The more recently Abbasi et al ( 11 ) found C. psittaci genotype B in symptomatic pigeons by partial sequencing of ompA in the North of Iran. Several studies identified C. psittaci genotype B in pigeons by PCR in different countries including the Netherlands ( 4 ), Belgium, Germany and Italy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is the same as our results when the majority samples were grouped under genotype B in pigeons. The recent experiments found whole genomic sequences of C. avium isolated from pigeons in Italy ( 32 ), the Netherlands ( 4 ) and Switzerland ( 5 ) by PCR. Further experiments should be done to determine the zoonotic ability and the virulence of this strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation